A numerical study of a suspended compound droplet solidifying under forced convection. (1st November 2022) - Pham, Binh D.; Vu, Truong V.
Highlights: A suspended compound droplet solidifying under forced convection is numerically studied. A supercooling nucleus at the droplet bottom causes the solidification. Increasing the size of the nucleus or the inner core enhances the solidification process. Increasing the strength of forced convection prolongs the normalized solidification time. Decreasing ϕgr or increasing ρsl decreases the outer aspect ratio of the solidified droplet. Abstract: In this study, we numerically investigate the solidification process of a suspended compound droplet in a cold environment under forced convection by a front-tracking method. The compound droplet consisting of an inner gas core (i.e., inner bubble) surrounded by a phase-change liquid shell (i.e., outer droplet) starts solidifying from a nucleus at its bottom. The phase-change interface evolves upward to form the solid shell with an upper conical outer surface due to volume expansion. We monitor main parameters such as the Reynolds number ( Re ) in the range of 25–200, the Stefan number ( St ) in the range of 0.05–1.6, the inner-to-outer radius ratio ( R io ) in the range of 0.2–0.7, the solid-to-liquid density ratio ( ρ s1 ) in the range of 0.8–1.2, the nucleus size ( r 0 / R ) in the range of 0.05–0.3, the initial eccentricity ( ε 0 ) in the range of -0.15–0.3 and the growth angle ( ϕ gr ) in the range of 0°–15°. It is found that an increase in St, ρ sl or a decrease in ϕ gr leads to a decrease in the height of the solidified droplet. In contrast, an increase in Re, r 0 / R, ε0 or R io has a minor effect on the drop height after complete solidification. In contrast to ρ sl, which has less influence on the solidification time, the change in the value of these parameters considerably modifies the solidification time. The inner and outer aspect ratios of the solidified droplet are also revealed.